Prediksi Harga Bitcoin Menggunakan Metode Random Forest : (Studi Kasus: Data Acak Pada Masa Pandemic Covid-19) - Siti Saadah; Haifa Salsabila (Politeknik Caltex Riau, 2021)
During this pandemic, virtual financial transactions increased sharply. Because the storage of assets and forms of buying and selling transformed using digital services. Bitcoin as one of the cryptocurrencies that is currently widely used and in demand by the people of the world, but there is no specialized financial institution responsible for bitcoin buying and selling transactions, requires a bitcoin price prediction system to know the status of the value of bitcoin. Referring to the ever-fluctuating characteristics of bitcoin data, the Random Forest Regression method is used to predict the price of bitcoin. This algorithm is one of the modeling that can produce good performance in terms of prediction. Using Random Forest Regression modeling, MAPE value was obtained by 1.50% with accuracy of 98.50%. That value is the value that produces the best performance among all bitcoin prediction attempts.